The Influence of Work Motivation, Salary, and Work Environment on Teacher Discipline in Private Junior High Schools: A Quantitative Study in Sub Rayon 09 Semarang City - Irawati, Nurul; Buchori, Achmad; Soedjono, Soedjono (FKIP - Universitas Riau, 2025)
This study examines the influence of work motivation, salary, and work environment on the work discipline of teachers in private junior high schools within Sub Rayon 09, Semarang City. The research employed a quantitative approach using survey methods with data collected through questionnaires distributed to teachers. Data analysis was carried out using multiple regression techniques to test the partial and simultaneous effects of the independent variables on teacher discipline. The findings revealed that work motivation had a positive and significant effect on teacher discipline, indicating that teachers with higher motivation tend to demonstrate stronger discipline in their professional responsibilities. Salary showed a positive but relatively small effect, suggesting that financial rewards still contribute to discipline, although not dominantly. Meanwhile, the work environment had a significant positive impact, emphasizing that conducive and supportive working conditions encourage discipline. Simultaneously, the three variables significantly influenced teacher discipline, with motivation emerging as the most dominant factor. These results highlight the importance of integrating intrinsic and extrinsic factors to enhance teacher discipline in educational settings.